Formação de professores de Letras: as crenças de um grupo de alunos sobre aprendizagem de língua inglesa - Bertucci, Marli Lorenzini (2009)
The aim of this work was to identify some beliefs of students of Initial Education in Languages – English and Portuguese about teaching and learning of a foreign language. This way I tried to understand what the ways those students consider appropriate for the learning of that language, setting up relations with the initial education of that graduate training. To reach the objective I looked support up in two theoretical bodies: the field of teachers’ education talking with authors as Nóvoa (1995); Josso (2004) , Furlanetto (2003) e Tardif (2002) among others, and in the Linguistics field examining the works of authors as Almeida Filho (1993,1999,2001,2002), Barcelos(1999;2004), Feiman-Nemser & Floden ,(1986), Vieira-Abrahão(2001,2004) among others. I adopted a qualitative approach to research and as data collection procedure I did a review of the literature on teacher education and in the beliefs about language learning through reading books, articles, theses and dissertations.I have also listened ten students of initial education in languages English and Portuguese by a questionnaire composed of open questions dealing about teaching and learning of a foreign language. I also researched to my professional life history through reflection on my own practice to understand not only the beliefs of the students, but also those ones are guiding my path training. It was possible to consider that some of the beliefs about the ideal way to learn a foreign language, in general does not differ from beliefs about how to learn the contents of other subjects:: we must have, among other things, interest, dedication and appropriate methodology. Another important consideration is that the beliefs presented by students have relations with conceptions of learning and teaching that were built by each one in social contact, especially in the social universe in the family and at school. Apparently also plays important role in how these students perceive the learning of language, the understanding of “learning as a gift” and also the difficulties arising from social exclusion.